2020
DOI: 10.1167/tvst.9.11.22
|View full text |Cite
|
Sign up to set email alerts
|

Reasons why OCT Global Circumpapillary Retinal Nerve Fiber Layer Thickness is a Poor Measure of Glaucomatous Progression

Abstract: Purpose To assess the effects of local defects, segmentation errors, and improper image alignment on the performance of the commonly used optical coherence tomography (OCT) measure of progression, that is the change in global (average) circumpapillary retinal nerve fiber layer (cpRNFL) thickness (ΔG). Methods One hundred fifty eyes suspected of, or with, early glaucoma had OCT circle and cube scans obtained using eye tracking on two occasions at least 1 year apart. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Formal testing of various OCT thickness measures with regard to the detection of glaucoma in such eyes showed lower performance for most such OCT measures, including macular thickness measures. 12 , 37 The lower performance of GCL as compared with GCIPL could also be explained by segmentation and alignment errors in the inner macular layer, 38 , 39 as well as concurrent changes within the IPL in early glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Formal testing of various OCT thickness measures with regard to the detection of glaucoma in such eyes showed lower performance for most such OCT measures, including macular thickness measures. 12 , 37 The lower performance of GCL as compared with GCIPL could also be explained by segmentation and alignment errors in the inner macular layer, 38 , 39 as well as concurrent changes within the IPL in early glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we and others have shown that subtle segmentation errors, which are difficult to detect, are common, and can lead to false diagnoses from the OCT summary metrics. 41 43 Second, if the scan is not placed properly on the disc or foveal center it can too lead to false diagnoses. 44 Third, early glaucomatous damage often involves relatively local defects that are missed by summary statistics, which include regions larger than these defects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly for OCT, it has been suggested as a general rule of thumb that a loss of 5 µm on the global cpRNFL between two OCT scans constitutes strong evidence of progressive glaucomatous loss, 11 , 12 although this measure has been questioned. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%